Developing agility and quickness (Human Kinetics, 2019)
As the world`s leading organization in the field of sport conditioning, the National Strength and Conditioning Association (NSCA) is at the forefront of such knowledge. In Developing Agility and Quickness, Second Edition, 19 of the NSCA`s leading experts provide evidence-based assessment tools, exercises, drills, and training regimens to achieve that aim: •More than 130 drills—with instructions, photos, and diagrams—offer a smorgasbord of proven activities to enhance athletes` ability to rapidly accelerate or decelerate in three dimensions. •Twelve agility and quickness tests provide gauges of present abilities and methods to measure progress. •Guidelines for tailoring training to specific needs present a blueprint for increasing change of direction speed and explosive movement. •New chapters on warm-up methods and age and sex considerations prepare athletes to get the most from their training. •Sport-specific training plans foster peak performance for athletes in 15 specific sports.